3-Methylbutyl 2-(5-iodo-3-methylsulfinyl-1-benzofuran-2-yl)acetate - Choi, Hong Dae (International Union of Crystallography, 2009)
In the title molecule, C(16)H(19)IO(4)S, the O atom and the methyl group of the methylsulfinyl substituent lie on opposite sides of the plane of the benzofuran fragment. In the crystal, pairs of molecules are linked by I⋯O [3.114 (3) Å] halogen bonding into centrosymmetric dimers. The crystal structure is further stabilized by weak intermolecular C—H⋯O nonclassical hydrogen bonds.